Roles and regulation of a Bdellovibrio bacteriovorus diguanylate cyclase, phosphodiesterase and a PilZ domain receptor. - Nottingham, Ruth (2017)
Cyclic-di-GMP is a ubiquitous second messenger regulating lifestyles across a wide range of bacteria, most notably motility and virulence. The components of c-di-GMP signalling networks are made up of: diguanylate cyclases (DGCs) that contain a GGDEF domain and make c-di-GMP, phosphodiesterases (PDEs) that contain an EAL or HD-GYP domain and break-down c-di-GMP and PilZ domains (or degenerate DGCs/PDEs) which are receptors for c-di-GMP.